The Role of Green Innovation on Environmental and Financial Performance in the Logistics Service Provider Industry - Meathawiroon, Chanchai (NIDA Business Journal, 2022)
The objective of this research study aims to develop a model regarding green innovation on environmental and financial performance in the logistics service provider industry. The target group in this research study consists of 287 representatives from the logistics service industry. In addition, the research hypothesis was tested via Structural Equation Modeling (SEM). This research study found that the model is related to the empirical data. The results from testing the hypothesis found that green service innovation and environmental performance have a positive influence on financial performance. Apart from this, green process innovation indirectly influences financial performance due to its positive impact on environmental performance. And this result also shows the theoretical contribution, the role of the mediator of environmental performance between green process innovation and financial performance in the logistics industry. Therefore, logistical service providers must bestow grant particular importance on the development or investment of green service innovations and green process innovation. this may be a factor that can generate a positive impact on the environment and financial performance. Consequently, this can also positively impact the business and create continual sustainable benefits for stakeholders in all sectors.